Geomorphological and Sedimentological Features of River Sadong, Sarawak, Malaysia - Omolayo Ajoke Omorinoye; Zaini Bin Assim; Ismail Bin Jusoh (Indonesian Journal on Geoscience, 2021)
DOI: 10.17014/ijog.8.1.119-130The effect of topography, climate, soil, and geology on River Sadong sediments is related to its geochemistry. Eighteen surface sediments and five core samples were collected in replicates from six sampling sites along River Sadong, Sarawak, Malaysia. The main aim of this study is to describe the geomorphology and sedimentological characteristics of the river sediments. This was achieved by the study of the processes that form the sediments and influence their physical and chemical characteristics. The sediments were analyzed for their sedimentological characteristics. The results indicated that the studied area is enriched with organic matter, and there are no sedimentary structures in its vicinity.